EFEKTIVITAS PENYELESAIAN PELANGGARAN ADMINISTRATIF PEMILIHAN UMUM BERDASARKAN UNDANG-UNDANG NOMOR 7 TAHUN 2017 - Evi Noviawati; Mamay Komariah (JURNAL ILMIAH LIVING LAW, 2019)
The Elections (Elections) in Indonesia is a process of democratization to elect national leaders and people's representatives who are elected directly by the people. The process of organizing the General Election is carried out through the stages stipulated in the Election Commission Regulation. One of the stages that must be passed in the holding of elections is the implementation of campaigns that are part of the political education of the community. In the implementation of an election campaign, election participants can form a campaign team that is responsible for the technical implementation of the campaign. Election administrative violations often occur in the stages of the campaign carried out by election participants which can consequently be detrimental to the election organizers and fellow election participants. Every settlement of election administrative violations can be decided by the Election Supervisory Body (Bawaslu) no later than 7 (seven) working days after the findings and reports are received and registered and then recommended to the KPU for further action. In reality on the ground, there are still many cases of election administrative violations that cannot be resolved due to several obstacles faced, namely the difficulty of finding the reporting party and the limited time in the process of filing reports and findings